Clinical efficacy of low level laser therapy in reducing pain and swelling after periapical surgery. A preliminary report. - Lilia Escalante-Macías; Verónica Méndez-González; Claudia Dávila-Pérez; Daniel Chavarria-Bolaños; Amaury Pozos-Guillén (Universidad de Concepción., 2015)
The objective of this study was to evaluate the efficacy of the low level laser therapy (LLLT) in postoperative pain and swelling associated with periapical surgery. A double-blind, randomized, controlled clinical trial was carried out in 2 groups of 10 patients each, undergoing periapical surgery. The experimental group was treated with an intraoral application of an 810nm-GaAsAl-laser, having an output power of 100mW, with overlapping movements over the wound. In the control group, the same procedure was carried out, without therapeutic laser activation. Postoperative pain, swelling, and rescue medication were registered. The experimental group exhibited a decrease in pain intensity after periapical surgery compared with control group (p<0.05). There was not significant statistical difference between the groups in terms of swelling. Six patients of the control group required rescue medication. The use of LLLT in the postoperative management of patients having periapical surgery, using the protocol of this study reduced postoperative pain.